Model Komunikasi Kepemimpinan dalam Manajemen LPP TVRI Stasiun Yogyakarta - Dewi, Lia Kartika; Sosiawan, Edwi Arief; Suparno, Basuki Agus (Jurnal Mahasiswa Komunikasi Cantrik, 2024)
Public Broadcasting Institutions (LPP) such as Televisi Republik Indonesia (TVRI) require quality human resources (HR) and requires good organizational communication. This is determined, among others, through the leadership model implemented. This study aims to examine the communication of leadership models in public broadcasting institutions. The research method used is qualitative with a case study strategy. The research was conducted at LPP TVRI Yogyakarta Station. Data were collected through in-depth interviews, documents, and literature. The results of the study show that leadership communication at TVRI Yogyakarta is determined by three strategic positions, namely the Head of Station as the leader of the organization related to regulations and policies and tends to be bureaucratic; the Head of the Sub-Section of Administration related to administration; and the Team Leader related to the freedom of creativity in broadcast program production and related to effective bureaucratic simplification.